Zikir Tahlil dalam Praktik Atib Koambai pada Masyarakat Kecamatan Kubu Babussalam, Kabupaten Rokan Hilir, Riau dalam Perspektif Ulama Tafsir - Wulandari, Winda (YASIN, 2023)
This study aims to determine the nature or concept of remembrance of tahlil in the practice of Atib Koambai according to the interpretation of scholars, according to the understanding of the people of Kubu Babussalam District, and the common ground between the two. The method used in this study uses the field research method (Field Research) with a qualitative descriptive approach presented in the form of a description of the words (description). The findings show that according to interpretation scholars, remembrance of tahlil is remembering Allah with the heart, mouth and limbs by carrying out orders and avoiding His prohibitions. Zikir tahlil means remembering the oneness of Allah and thinking about His creation, by reciting it will strengthen the heart, increase obedience and gratitude for all the blessings that Allah has given. Recitation of tahlil according to the understanding of the Babussalam community is remembering Allah and all of His creation, believing that helping Allah can be achieved by reciting Him as a form of worship and drawing closer to Allah. By reciting the remembrance of tahlil which is believed and understood as the most afdal remembrance and has many virtues when practicing it as explained by the scholars. From there, the local clerics and the community might conclude that the tahlil sentence is the most effective dhikr to raise reinforcements because Atib Koambai itself was carried out because of reinforcements and disease outbreaks.